Analysis of the Performance of the Agribusiness Subsystem in the Development of Horticultural Commodities in Kehiran Village - La Maga; Hans Z. Kaiwai; Mellyanti Eka Putri (AIBPM Publisher, 2025)
The agribusiness sector plays a strategic role in producing food for the community. The agribusiness sector consists of several interrelated subsystems. When a disruption occurs in one subsystem, it will affect the other subsystems. The purpose of this study was to analyze the performance of the agribusiness subsystem in vegetable farming in Kehiran Village, East Sentani District, Jayapura Regency. Based on the results of the study, it shows various agribusiness index scores, namely: the production input procurement subsystem was 15.80, the farming subsystem was 19.90, and the marketing subsystem was 5.80. All four subsystems are in the good category. The service and support subsystem index was 4.55, indicating a poor category. The agribusiness system index score in vegetable farming was 13.486. The maximum value of the agribusiness system was 18.090, so the performance of the agribusiness system in vegetable farming was in the poor category. Based on this, the development of vegetable farming in Kehiran Village must be supported by other aspects. For example, ease of access to capital loans for farmers, intensity of extension activities, formation of farming cooperatives, and the active role of farmer groups as a means of learning and a source of information for farmers.